Transdisciplinary Synergy in Inclusive Early Childhood Education: Integrating Special Education Expertise and Strategic Management for Service Quality - Dewi Cahyaningrat; Dian Sudiantini; Azlan Bin Saflie (Jurnal Pendidikan Anak, 2026)
Purpose: This study aims to analyze the convergence between early childhood special education expertise and strategic management science—viewed as a social-institutional factor—on inclusive early childhood education (ECE) management and its subsequent impact on service quality for children with disabilities in Serang City, Banten Province, Indonesia. Methodology: This quantitative explanatory study involved 168 respondents (38 principals and 130 teachers) from 38 ECE institutions selected through purposive sampling. Data were collected using structured questionnaires with a five-point Likert scale and analyzed using PLS-SEM with SmartPLS 4.0. Instrument content validity was ensured through expert judgment by three academic panelists. Findings: The results demonstrate that educational leadership with special education insight (β = 0.394; p < 0.001), strategic management functions adapted for inclusivity (β = 0.331; p < 0.001), and multi-sector stakeholder collaboration (β = 0.317; p < 0.001) positively influence inclusive ECE management. Inclusive ECE management significantly enhances educational service quality (β = 0.578; p < 0.001). The collaboration between these distinct disciplines explains 71.4% of the variance in inclusive ECE management (R² = 0.714). The study confirms that collaborative capability serves as a Valuable, Rare, Inimitable, and Non-substitutable (VRIN) strategic resource. Implications: The findings emphasize the critical importance of transdisciplinary synergy between special education specialists and strategic management practitioners. Recommendations include establishing interdisciplinary teams at the institutional level, developing integrated training programs, and designing collaborative policy frameworks to foster sustainable institutional change. Originality/Value: Grounded in the Resource-Based View (RBV) theory, this research provides the first empirical evidence regarding the synergistic value of combining management science and special education within the K-12 ecosystem. It demonstrates that social-institutional factors, driven by expertise collaboration, are the primary keys to effective inclusive education.